Edward Telfair grants - Telfair, Edward, approximately 1735-1807.
Land grants issued by Telfair as governor of Georgia to Samuel Beckcom, Benjamin Kitchen, Israel Robinson, and Francis Tennil; and two Georgia state seals.
Indian commissioner, delegate to the Continental Congress, and governor of Georgia.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Beckcom, Samuel; Kitchen, Benjamin; Robinson, Israel; Tennil, Francis; Land grants -- Georgia; Georgia -- Seal; Delegate, U.S. Continental Congress -- Georgia; Governors -- Georgia; Indian commissioners